Textes constitutionnels de la Ve République : à jour de la Charte de l'environnement. - Rials, Stéphane; Mathieu, Bertrand; Verpeaux, Michel (Paris : PUF, 2005)
Bibliotheek François Vercammen
Frans
Monografie